2020
DOI: 10.1302/0301-620x.102b2.bjj-2019-0692.r2
|View full text |Cite
|
Sign up to set email alerts
|

Better outcome for suture button compared with single syndesmotic screw for syndesmosis injury: five-year results of a randomized controlled trial

Abstract: Aims In a randomized controlled trial with two-year follow-up, patients treated with suture button (SB) for acute syndesmotic injury had better outcomes than patients treated with syndesmotic screw (SS). The aim of this study was to compare clinical and radiological outcomes for these treatment groups after five years. Methods A total of 97 patients with acute syndesmotic injury were randomized to SS or SB. The five-year follow-up rate was 81 patients (84%). The primary outcome was the American Orthopaedic Foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
90
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 127 publications
1
90
2
Order By: Relevance
“…Raeder Raeder et al reported high rates of syndesmosis malreduction, 70% in the SS group and 72% in the SB group, at five years. Moreover, unlike our findings, Reader et al found an increase in the overall malreduction rate during follow-up, from postoperative (32%) to five years (71%); however, the malreduction rates per group were only reported at five years [24] . The high malreduction rates in that study might be due to syndesmosis screw removal; they removed the SS after a mean of 85.9 days postsurgery, which might explain the late widening of the syndesmosis described earlier by Schepers et al (2011) and Hsu et al (2010) [ 24 , 37 , 38 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Raeder Raeder et al reported high rates of syndesmosis malreduction, 70% in the SS group and 72% in the SB group, at five years. Moreover, unlike our findings, Reader et al found an increase in the overall malreduction rate during follow-up, from postoperative (32%) to five years (71%); however, the malreduction rates per group were only reported at five years [24] . The high malreduction rates in that study might be due to syndesmosis screw removal; they removed the SS after a mean of 85.9 days postsurgery, which might explain the late widening of the syndesmosis described earlier by Schepers et al (2011) and Hsu et al (2010) [ 24 , 37 , 38 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In their study, 11 patients had the SB removed before the two-year follow-up visit, but the exact timing of removal was not reported [ 19 , 24 ]. Moreover, their method for detecting syndesmosis malreduction was different than ours, but that does not explain the increasing rate of malreduction during follow-up, which was not observed in our study [24] . Our low malreduction rates in both the SS and SB groups were probably due to the experienced orthopaedic trauma surgeons, who performed all the operations during office hours, and the assessment of syndesmosis reduction with intraoperative CT of both ankles.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Today, surgical treatment consists of closed reduction of the distal tibiofibular joint and indirect fixation, either static or dynamic. Although static fixation by means of one or two syndesmotic screws is considered to be the most common procedure, emerging evidence points at a superior patient reported outcome for the dynamic fixation by a suture button system [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, SFD has been shown to provide adequate fixation in cadaveric and clinical studies, and there are also publications indicating better functional results than screws. [ 21 ] The major disadvantage of using SFD is its cost and low availability compared with screws and is probably the reason for its limited use in this survey. Although the cost of SFD is higher than screws, when secondary procedures for device removal are considered, the cost for dynamic fixation has been found to be lower.…”
Section: Discussionmentioning
confidence: 99%